To Assess The Accuracy Of Radiology Procedure Codes For Standardization And Structure Of Radiology Department - Ummara Siddique Umer, Muhammad Asif, Muhammad Salman Rafique, Abdullah Safi, Mahwish Jabeen, Sana Kundi, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To see accuracy of radiology procedure codes for standardization and structure of radiology department Methods: 100 cases for each procedure i.e. radiology, fluoroscopy, MRI and CT scan were selected. Request forms were reviewed and the assigned codes were compared with the films of radiology on a system called picture archiving and communication system (PACS). This system determines the appropriate coding. Results: In this study, accurate coding in MRI, fluoroscopy, CT scan and X rays was 99%, 95%, 90% and 85% respectively according to local guidelines. Conclusion: This study concludes that MRI has maximum accuracy i.e. 99% and x rays have minimum i.e. 85%.